ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA (Studi Kasus Pada Perusahaan Non Keuangan Yang IPO Di Bursa Efek Indonesia Tahun 2016) - Mahfiro Mahfiro; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study is to explain the difference in financial performance of non-financial companies before and after their initial public offering (IPO) on the Indonesia Stock Exchange (BEI). This study applies a quantitative approach with statistical methods. Research variables consist of Current Ratio (CR), Debt Ratio (DER), Debt Ratio (DR), Total Asset Turnover (TATO), Net Return (NPM), Return on Investment (ROI), and Return on Equity.  Data analysis is a descriptive statistical analysis, which is an inference statistical analysis consisting of hypothesis testing and hypothesis testing using SPSS version 20. The results of the hypothesis test using the paired t test show that there is a large difference in the financial performance of the company before and after the IPO. Viewed from average CR and ROE. On the other hand, looking at the average values of DER, DR, TATO, NPM, and ROI, there is no big difference in the financial performance of the company before and after the IPO. Overall, the company's financial performance has not improved since the IPO. This may be due to the short observation period and the condition of the company still in the adjustment stage after the IPO.Keywords: Financial Performance, Initial Public Offering, IPO, BEI, Financial Ratio